Bio-inspired design for engineering applications: empirical and finite element studies of biomechanically adapted porous bone architectures - Aguirre, Trevor Gabriel, author; Donahue, Seth W., advisor; Ma, Kaka, committee member; Heyliger, Paul, committee member; Simske, Steven, committee member (Colorado State University. Libraries, 2020)
Trabecular bone is a porous, lightweight material structure found in the bones of mammals, birds, and reptiles. Trabecular bone continually remodels itself to maintain lightweight, mechanical competence, and to repair accumulated damage. The remodeling process can adjust trabecular bone architecture to meet the changing mechanical demands of a bone due to changes in physical activity such as running, walking, etc. It has previously been suggested that bone adapted to extreme mechanical environments, with unique trabecular architectures, could have implications for various bioinspired engineering applications. The present study investigated porous bone architecture for two examples of extreme mechanical loading. Dinosaurs were exceptionally large animals whose body mass placed massive gravitational loads on their skeleton. Previous studies investigated dinosaurian bone strength and biomechanics, but the relationships between dinosaurian trabecular bone architecture and mechanical behavior has not been studied. In this study, trabecular bone samples from the distal femur and proximal tibia of dinosaurs ranging in body mass from 23-8,000 kg were investigated. The trabecular architecture was quantified from micro-computed tomography scans and allometric scaling relationships were used to determine how the trabecular bone architectural indices changed with body mass. Trabecular bone mechanical behavior was investigated by finite element modeling. It was found that dinosaurian trabecular bone volume fraction is positively correlated with body mass like what is observed for extant mammalian species, while trabecular spacing, number, and connectivity density in dinosaurs is negatively correlated with body mass, exhibiting opposite behavior from extant mammals. Furthermore, it was found that trabecular bone apparent modulus is positively correlated with body mass in dinosaurian species, while no correlation was observed for mammalian species. Additionally, trabecular bone tensile and compressive principal strains were not correlated with body mass in mammalian or dinosaurian species. Trabecular bone apparent modulus was positively correlated with trabecular spacing in mammals and positively correlated with connectivity density in dinosaurs, but these differential architectural effects on trabecular bone apparent modulus limit average trabecular bone tissue strains to below 3,000 microstrain for estimated high levels of physiological loading in both mammals and dinosaurs. Rocky Mountain bighorn sheep rams (Ovis canadensis canadensis) routinely conduct intraspecific combat where high energy cranial impacts are experienced. Previous studies have estimated cranial impact forces up to 3,400 N and yet the rams observationally experience no long-term damage. Prior finite element studies of bighorn sheep ramming have shown that the horn reduces brain cavity translational accelerations and the bony horncore stores 3x more strain energy than the horn during impact. These previous findings have yet to be applied to applications where impact force reduction is needed, such as helmets and athletic footwear. In this study, the velar architecture was mimicked and tested to determine suitability as novel material architecture for running shoe midsoles. It was found that velar bone mimics reduce impact force (p < 0.001) and higher energy storage during impact (p < 0.001) and compression (p < 0.001) as compared to traditional midsole architectures. Furthermore, a quadratic relationship (p < 0.001) was discovered between impact force and stiffness in the velar bone mimics. These findings have implications for the design of novel material architectures with optimal stiffness for minimizing impact force.
Keywords: big horn sheep; bone strength; trabecular bone; bio-inspired design; allometry; finite element modeling